A new genus and a new species of Trigonidiidae (Orthoptera: Grylloidea) from north Myanmar amber - Yuan, Wei; Ma, Li-Bin; Gu, Jun-Jie (Zootaxa, 2023)
We present the description of a new genus and new species of Trigonidiidae, Qiongqi crinalis gen. et sp. nov., found in amber deposits at Noije Bum, near Tanai in the Hukawng Valley of northern Myanmar. Its lateralized eyes, short clypeus, exposed mandible, and extremely dense setae entirely covering the body, provides us with new knowledge on the morphology of Trigonidiidae. Additionally, a key to species of fossil Trigonidiidae in amber was provided.